Preventing COVID-19 Collateral Damage - Shepherd, James (Clin Infect Dis, 2020)
The lockdown in response to coronavirus disease 2019 (COVID-19) risks damaging the response to many infectious diseases. We recommend integrating the COVID-19 response into existing public health programs, strengthening both.